Branching 'Maxi Gala' apple tree grafted on several clonal rootstocks - Marchioretto L.R. (2020)
© 2020 International Society for Horticultural Science. All rights reserved.Plant growth regulators (PGRs) have been used to boost apple yield and fruit quality, however, further studies need to be carried out to improve tree quality in the nursery. This experiment aimed to establish a protocol to produce well feathered trees with a minimal length of the shoots approximately of 20 cm. The experiment was carried out in 2015/2016 and 2016/2017. On both years, trees were sprayed every 15 days beginning when the plant height reached 50 cm above the graft union. In the first year, the treatments (full rate of active ingredient) were: benziladenine (BA), GA+BA4+7 at rates of 250, 500 and 750 ppm, and thidiazuron at rates 25, 50 and 75 ppm, all treatments were sprayed five times as a directed spray on the apical meristem. In the second year, BA was tested at 500 ppm (four times), 1500 ppm (two times), and 1000 ppm (four times); BA+GA4+7 at 500, 1000 and 1500 ppm (five times); and cyclanilide + ethephon at 12.5, 25 and 37.5 ppm (two times). In both seasons, the PGRs were compared with an untreated control. The sprays were done on the apical meristem of 'Maxi Gala' apple trees grafted on the rootstocks: M.9, Marubakaido/M.9 interstem, G.202 and G.213. The parameters evaluated were number of branches and branch length. The use of benzyladenine alone or associated with GA4+7 is more effective in promoting the emission of branches in apple trees in all rootstocks. As evaluated in the two years of the experiment, the best BA dose was between 750 and 1000 ppm, being more effective than BA+GA4+7, which requires higher rates to promote the same effect, around 1000 to 1500 ppm. The use of benzyladenine promotes the emission of more compact branches than BA+GA4+7, being able to indicate the possibility of production of trees containing spurs. The G213 rootstock exhibited the greatest ability to emit lateral branches in relation to M.9 and G202, even without PGRs.